The Correlation Between Sociodemographic Status, Attitudes, and Family Behavior with the Status of PSN (Eradication of Mosquito Breeding Sites) Regularity of Endemic Dengue Fever in the Area of Purwokerto Barat - Serin Dwi Ranesta; Ragil Setiyabudi (Proceedings Series on Health & Medical Sciences, 2024)
Background: Dengue Fever (DF) is an endemic disease in Indonesia, especially in tropical climate regions, and remains a significant public health issue. The cases of DF from 2019 to 2022 have shown fluctuating trends. Dengue fever prevention involves efforts such as the Eradication of Mosquito Breeding Sites (PSN), where the success of PSN is measured by the Larval Free Index (LFI), aiming to achieve the government target of LFI 95%. Method: This study employed a quantitative research approach with a correlational design using a cross-sectional approach. The study population in West Purwokerto. The sample was 110 respondents using the Lemeshow formula. The instrument included a questionnaire sheet and was analyzed using the Chi-square test. Results: The majority of respondents are around 45 years old with a regular PSN status (58.2%), have a high school education (56.4%), are unemployed (62.7%), have a low income (53.6%), and exhibit infrequent mobility (84.5%). The respondents generally display positive attitudes (90%) and good family behavior (59.1%). The findings indicate a correlation between sociodemographic factors such as age (p=0.020), education (p=0.001), occupation (p=0.03), household income (p=0.035), but no correlation with mobility (p=0.187), and the status of PSN regularity. There is a correlation between attitudes (p=0.026) and family behavior (p=0.0001) with the status of PSN regularity in the West Purwokerto Region. Conclusion: There is a correlation between sociodemographic factors, including age, education, occupation, household income, and the status of PSN regularity. There is a relationship between attitudes and family behavior with the status of PSN regularity.